2016
DOI: 10.1007/s12410-016-9385-x
|View full text |Cite
|
Sign up to set email alerts
|

Normal Databases for the Relative Quantification of Myocardial Perfusion

Abstract: Purpose of review Myocardial perfusion imaging (MPI) with SPECT is performed clinically worldwide to detect and monitor coronary artery disease (CAD). MPI allows an objective quantification of myocardial perfusion at stress and rest. This established technique relies on normal databases to compare patient scans against reference normal limits. In this review, we aim to introduce the process of MPI quantification with normal databases and describe the associated perfusion quantitative measures that are used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…It is customary to use separate, normal databases specific to the imaging camera, the reconstruction method, the patient's gender, as well as the perfusion agent used. 119 This quantitative analysis is typically displayed as a ''bullseye'' or polar plot. The quantitative programs are effective in providing an objective interpretation that is inherently more reproducible than visual analysis, eliminates the variability of the appearance of a defect when viewed in different media (with different radiotracers) and different translation tables, and is particularly helpful identifying subtle changes between two studies in the same patient.…”
Section: 116mentioning
confidence: 99%
“…It is customary to use separate, normal databases specific to the imaging camera, the reconstruction method, the patient's gender, as well as the perfusion agent used. 119 This quantitative analysis is typically displayed as a ''bullseye'' or polar plot. The quantitative programs are effective in providing an objective interpretation that is inherently more reproducible than visual analysis, eliminates the variability of the appearance of a defect when viewed in different media (with different radiotracers) and different translation tables, and is particularly helpful identifying subtle changes between two studies in the same patient.…”
Section: 116mentioning
confidence: 99%
“…Thus, a potential limitation of this quantitative approach is the need for system-specific, protocol-specific, dose-specific, and gender-specific databases of normality. 18 Very recently, different studies have shown that to compare data from the analysis of polar maps across different systems or different configuration of the same system will require the adoption of specific databases of normality, developed for each system and reconstruction method employed. 19,20 On the contrary, if the database of normality should be specific also for the dose level of the study is still an open question today.…”
Section: Specific Database Of Normality For the Reconstruction Stratementioning
confidence: 99%
“…In the recent review of quantification with normal limits, Rubeaux et al summarized the developments with regards to specific normal limits related to the new equipment and imaging protocols. 9 The key parameters defining the characteristics of the normal database are the camera type, count level (low-dose vs high-dose affecting the variation of the normals), 10 attenuation correction (yes/no), patient position (as studied by Kracsko et al), 5,7,8,11,12 and possibly patient ethnicity. For example, an extensive validation of Japanese-specific databases [13][14][15][16] clearly demonstrated the need for the creation of population-specific databases.…”
Section: Patient Position and Normal Perfusion Appearancementioning
confidence: 99%